Plan de negocio para un motel temático en el cantón Latacunga. - Quispe Guanoluisa, Vilma Gissela (2019)
The main objective is to make a business plan for the thematic motel in Latacunga, analyzing its feasibility. In the market survey our potential customers is economically active population (EAP) men and women from 20 to 54 years old with incomes from a basic salary, where 85.1% of inhabitants have visited a motel, so the motel implementation would be widely accepted, Latacunga has an offer of 5 main motels that customers often visit more frequently, but the Kaffe´s motel is the most popular among customers thus being the most competitive for our business. It analyzed the degree of tastes and preferences in designs and styles of rooms (las mil y una noches, sabana africana, olimpo, la amazona, las pirámides de Egipto y fantasie) which all had a high level of acceptance by customers, in addition the services which the motel will have is the decoration, transportation, lingerie and sexual toys, the monetary rate they are willing to pay is a minimum of $10 and a maximum of $30 dollars preferentially paid in cash, its advertising will be via internet like (Facebook, Instagram, twitter), as a promotion our potential customers prefer discounts. In the technical study it analyzed the micro location, through the matrix of weighted factors where San Buena Aventura area is the right place for the motel installation that emphasizes the infrastructure, access roads, discretion and the labor requirements, furniture, equipment, facilities, computer equipment and office which are necessary to meet the necessities and expectations of potential customers for this type of services, the motel distribution will have 2 floors, which the facilities will have rooms with garage, administrative area, service area and green areas, 6 rooms will be thematic and have 24-hour bar service, television, Kama Sutra chair and 3 rooms will have Jacuzzi. In the financial study the first investment research will require a very considerable amount of money that is $ 102,787.36 dollars, this investment will be covered by two investors in 30% that contribute with their own capital of $ 30,836.21 and the remaining 70% will be requested to a financial entity with the amount of $ 71,951.15 at an interest rate of 11.83% for five years amortized annually. In the financial study the first investment research will require a very considerable amount of money that is $ 102,787.36 dollars, this investment will be covered by two investors in 30% that contribute with their own capital of $ 30,836.21 and the remaining 70% will be requested to a financial entity with the amount of $ 71,951.15 at an interest rate of 11.83% for five years amortized annually. This research financial evaluation presented important data such as the NPV of $ 26,649.23 positive and the IRR 16.54% on the opportunity with a recovery period of 3 years, 9 months and 7 days, which estimates that this research is fully feasible for its creation. The Cost Benefit Relationship shows that the entity for every dollar spent will obtain $1.10 dollars of profit which means that this research is feasible.